Use, management and local ecological knowledge of Sabal mauritiiformis in the Colombian Caribbean - Andrade Erazo, Viviana; Estupiñán-González, Ana; García, Néstor; Bernal, Rodrigo; Raz, Lauren; Galeano, Gloria (Ethnobiology and Conservation, 2020)
The leaves of the palm Sabal mauritiiformis constitute the natural material most used for thatching in the Colombian Caribbean. The leaves and other parts of the plant are also used in other economic and cultural activities on a smaller scale. Through 49 semi-structured interviews and seven days of participant observation, we documented the management and local ecological knowledge of this species in a Colombian peasant community, and identified the value chain for its leaves. We found 25 uses for S. mauritiiformis, belonging to 11 use categories. The leaves are harvested from wild populations, where the most outstanding management practice is tolerance, consisting of the maintenance of the palms in traditional production systems, even after the elimination of forest canopy. Leaf marketing results in an organized, simple and regional value chain, mainly linked to tourism. The relevance of this species in the Caribbean was evident both in the different management modalities and in the stock of ecological and technical knowledge that the communities have accumulated. This has allowed the conservation of this palm, despite the almost total disappearance of its natural habitat. With some adjustments in the practices applied to palms and to the value chain, the case of S. mauritiiformis in the Caribbean would constitute a model of how use and conservation of native biodiversity can contribute to boost regional economy.